Adipositas and metabolic bone disorder in a 16th century Upper Austrian infant crypt mummy—An interdisciplinary palaeopathological insight into historical aristocratic life - Nerlich, Andreas G.; Panzer, Stephanie; Wimmer, Judith; Hamann, Christian; Peschel, Oliver K. (Frontiers in Medicine, 2022)
We describe here the results of a multidisciplinary study on an infant mummy from 16th century Upper Austria buried in the crypt of the family of the Counts of Starhemberg. The macroscopic-anthropological, radiological (whole-body CT scan), histological (skin tissue) and radiocarbon isotope investigations show a male infant of 10-18 months’ age, dying most likely between 1551 and 1634 CE (probably Reichard Wilhelm, 1625-1626 CE), that presented with evidence for metabolic bone disease with significant flaring of costochondral joints resembling “rachitic rosary” of the ribs, along with straight long bones and lack of fractures or subperiosteal bleeding residues; although incompletely developed, the osteopathology is in favour of rickets without upper or lower extremities long bone deformation. The differential diagnosis is vitamin-C-deficiency (scurvy) (also with an incomplete presentation, although an overlap between both disorders may be present). As additional pathology there was significantly enlarged subcutaneous fat tissue (thickness more than 1 cm at the navel and thighs and longitudinal creases of the skin) along with a histologically enlarged subcutaneous fat layer consistent with infantile adipositas as a coincident disorder. Finally, remnants of lung tissue with pleural adhesion of the right lung indicate possibly lethal pneumonia, a disease with an increased prevalence in vitamin-D-deficient infants. Ultimately, the skull presented with extensive destruction of the bones of the base and dislocation of the bones of the skull squama. These changes, however, most presumably represent post-mortal pseudopathology, the consequence of a burial in a flat, narrow coffin as there were no bone fractures nor residues of bleeding / tissue reaction which would occur in life.